Analysis of Landing Error Scoring System and Lower Extremity Kinematic Variables during Drop Vertical Jump on Anterior Cruciate Ligament Injury Risk Factors in Elite Soccer and Taekwondo Players - Ji-Hoon Cho; Namwoong Kim; Sang-Won Seo (The Asian Journal of Kinesiology)
OBJECTIVES The purpose of this study was to compare the risk factors associated with anterior cruciate ligament (ACL) injuries in elite soccer and taekwondo players by examining landing error scoring system (LESS) scores and limb symmetry index (LSI). METHODS A total of 20 male athletes (10 soccer players and 10 taekwondo players) were evaluated. Participants completed a drop-landing task, and their landing mechanics were evaluated using the LESS. Muscle activation was measured with surface electrodes placed on the rectus femoris and biceps femoris. LSI values were calculated as a percentage based on muscle activation data, using the ratio of the nondominant limb to the dominant limb, to assess asymmetry. RESULTS Significant differences were observed between the two groups in knee valgus angle at initial contact (p=0.005), knee joint displacement (p=0.024), and overall impression (p=0.011). Notably, the soccer players demonstrated a significantly higher LESS score (total score, p=0.024) compared to the taekwondo players. However, no significant differences in LSI were found between the two groups. CONCLUSIONS The findings suggest that elite male soccer players may benefit from targeted interventions, such as neuromuscular control training, to enhance joint stability and correct landing mechanics, compared to taekwondo players.